Newnes mechanical engineer's pocket book - Timings, R. L. (Roger Leslie) (Newnes Pocket Books., 2006)
"The Mechanical Engineer's Pocket Book continues to keep pace with the many changes in technology and engineering design standards, and brings together all of the information that is required when designing and developing engineering products, devices and systems prior to manufacture. Substantially revised and restructured, the third edition covers the most recently introduced standards and latest technologies, with an increased emphasis on design, research and development, making it a vital resource for all engineers."--Jacket.